Analysis of the Use and Formation of Ryakugo in Takano Ichigo's Orange Comic. - Ulfa Lutfi Nauriyah; Yuni Masrokhah; Akbar Nadjar Hendra (Jurnal Bahasa Jepang Taiyou, 2021)
The abbreviated vocabulary seems more interesting and easier in spelling a long word. This abbreviation does not only occur in Wagoand Kango, but also in Gairaigo. This research aims to describe the type and process of forming and using Ryakugoin Japanese sentences comic. This research uses a descriptive method with a qualitative approach. The technique used in data collection is a library study technique, then a dissolving technique as data analysis. The object of this research is Orange comic by Takano Ichigo. The results of this study are two types of ryakugo, namely karikomiand toujigo. In addition, there are 13 processes of formation of ryakugo, whichare dissolving at the end of the word, dissolving in the middle of the word, dissolving on thebeginning of the word, dissolving two parts or more in a single word, dissolving on the ending at the second compound word, dissolving the part the end is only in the first compound word, dissolving of three or more parts in compound words, dissolving the ending at the end of each element of the compound word, shortening by phoneme dissolving, phoneme dissolution or syllable at the end of the word and experiencing assimilation, phoneme or silabelingin the middle the word then experiences assimilation, phoneme or syllable obliteration in the second word then undergoes assimilation, an abbreviation of the alphabet. The use of ryakugoin this comic is almost entirely done in informalconversations.